Regulation of skeletal muscle PPARδ mRNA expression in twins - Nilsson, Emma (Blackwell Science Inc, 2007)
Peroxisome proliferator-activated receptors (PPARs) are nuclear receptors regulating the expression of genes involved in lipid and glucose metabolism in a complex and to some extent unknown manner. Our aim was to study the impact of different factors on PPARδ mRNA expression in human skeletal muscle on one side, and the impact of PPARδ mRNA expression on these factors, including glucose and lipid metabolism, aerobic capacity, fibre type composition and lipid profile, on the other side. PPARδ mRNA levels were quantified by real-time PCR in muscle biopsies from 176 young and elderly monozygotic and dizygotic twins. Young twins had significantly increased PPARδ mRNA levels compared with elderly twins. A 2 h hyperinsulinaemic euglycaemic clamp had no significant effect on PPARδ mRNA levels. Biometric models were calculated for basal PPARδ mRNA expression to estimate the degree of genetic versus environmental influence. In both young and elderly twins there was a substantial genetic component influencing basal PPARδ mRNA levels. In a regression model, the muscle PPARδ mRNA expression was correlated to birth weight, central adiposity and age. The level of PPARδ mRNA was also positively correlated with markers for oxidative muscle fibres. However, in this apparently healthy study population, we found no correlations between PPARδ mRNA expression and aerobic capacity, lipid profile or glucose and lipid metabolism. In conclusion, we provide evidence that mRNA expression of PPARδ in human skeletal muscle is under genetic control but also influenced by factors such as age, birth weight and central adiposity.